Bovine Lactoferrin in the Prevention of Antibiotic-Associated Diarrhea in Children: A Randomized Clinical Trial - Wronowski, Michal F.; Kotowska, Maria; Banasiuk, Marcin; Kotowski, Artur; Kuzmicka, Weronika; Albrecht, Piotr (Frontiers in Pediatrics, 2021)
Introduction: Antibiotic-associated diarrhea (AAD) is a common adverse reaction to antibiotic treatment affecting up to 21% of children. The aim of the study is to evaluate whether bovine lactoferrin (bLf) might be used for AAD prevention. Materials and methods: In this prospective, randomized, double-blind, placebo-controlled, single-center study we enrolled 156 children aged between 1 and 18 years, treated with antibiotic due to acute respiratory or urinary tract infection. We randomly allocated children 1:1 to receive 100 mg of bLf or a placebo twice a day orally for the whole period of antibiotic therapy. The primary outcome was the occurrence of antibiotic-associated diarrhea during and up to two weeks after antibiotic therapy. The secondary endpoint was intravenous rehydration or antibiotic withdrawal due to diarrhea. We performed an intention-to-treat analysis. Results: We included 150 patients in the intention to treat analysis. AAD occurred in 16 of 75 (21,3%) patients in bLf group and in 7 of 75 (9,3%) individuals in placebo group (OR 2.6 [95% CI 1.01 – 6.84] p 0.04). Relative risk was 2.29 (95%CI 0.89 to 5.88). The need for intravenous rehydration occurred in 1 patient in the placebo group (p 0.3). We observed no adverse effects in neither of the groups. Discussion: The trial indicated that bLf is not effective in AAD prevention. The risk for AAD was higher in the bovine lactoferrin group as compared to the placebo. We registered the study protocol on clinicaltrials.gov - NCT02626104.